PENGEMBANGAN GAME EDUKASI PADA MATERI TEKNOLOGI INFORMASI DAN KOMUNIKASI KELAS X DI SMK NEGERI 5 PADANG - Wahyuni, Sindi Mardia; Mary, Thomson; Pratama, Ade (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This research uses Research and Development (R D) research with the ADDIE development model which consists of 5 stages, namely, Analysis (Analysis), Design (Design), Development (Development), Implementation (Implementation) and Evaluation (Evaluation). The ADDIE model concept is applied to develop a learning product design. The media validation results obtained an average score of 82.22% in the